Factors affecting smallholder grain production in the Ethiopian highlands - Anderson, F.M.; Gryseels, Guido; Durkin, J.W. (OAU/STRC, 1987)
Discusses factors influencing grain production in a representative and risky farming system in the Ethiopian highlands, with quantitative evidence of the critical contribution of draft oxen to farm grain production by comparing yield and area cultivated between farmers who are ox-owners and those who are not.